Lesions in blunt abdominal trauma at Cusco, Peru - Dueñas, José (2002)
Objective: To identify intraabdominal injuries in blunt abdominal trauma and to characterize this trauma at high altitude. Material: We analyzed 99 cases occurring from 1964 to 1999. Results: Young adults predominated, 73% of them males, mainly workers and students. Main cause was traffic accidents (51,5%) and main symptoms abdominal pain (90,9%), nausea and vomiting (31,3%), shock (29,3%), as well as, abdominal distention, hematuria, abdominal wall resistance. Organ injuries occurred in small bowel (28,3%), liver (25,3%), bladder (18,2%), mesenterium (14,1%), spleen (12,1%). Hospital stay was usually 11 to 12 days, 35,7 days average. Conclusions: Mortality rate was 8,1%, and pre- and post-operative diagnosis correlation occurred only in 37,4% of cases.